The Profiles of Blood Pressure and Blood glucose Level among the Elderly in “Y” Village, Gresik, Indonesia - Putri Ayuni Alayyannur1 , Festi Artika Sari2 , Nova Febriana3 , Rohmat Romadhoniansyah4 , Fajar Muha (Indian Journal of Forensic Medicine & Toxicology, 2020)
Elderly people is someone who has the age of 60 years or more. In old age physiological functions decrease due to degenerative processes (aging), resulting in many non-communicable diseases. Non-communicable diseases in the elderly include hypertension, stroke, diabetes mellitus and arthritis or rheumatism. The prevalence of hypertension and diabetes in the district of Gresik is quite high. The aims of this community service was to find out the profile of blood pressure and blood glucose levels of the elderly in “Y” Village, Gresik District. This study was a descriptive study with a cross-sectional design. The sampling method uses accidental sampling technique, which is 60 elderly people who come at the health examination. Sixty elderly people measured blood pressure and blood glucose level. The measurement results showed that the elderly blood pressure in Y village had 50% blood pressure in the hypertension stage 1 and 2, 23% in the pre hypertension category, and 27% had normal blood pressure. While the results of measuring 22% of blood glucose levels had blood glucose level in the Diabetes Melitus category which is ?200 mg / dl, 58% have blood glucose levels in the category of 90-199 mg / dl and 20% had normal blood glucose levels. This study concludes that most of the elderly in Y Village are suffering from hypertension and having non-DM blood glucose level. Conclusion of this research is elderly people in Y Village has hypertension and blood glucose level in the category of not yet diabetes.